CD24-Siglec interactions in inflammatory diseases - Liu, Yang; Zheng, Pan (Frontiers in Immunology, 2023)
CD24 is a small glycosylphosphatidylinositol (GPI)-anchored glycoprotein with broad expression in multiple cell types. Due to differential glycosylation, cell surface CD24 have been shown to interact with various receptors to mediate multiple physiological functions. Nearly 15 years ago, CD24 was shown to interact with Siglec G/10 to selectively inhibit inflammatory response to tissue injuries. Subsequent studies demonstrate that sialylated CD24 (SialoCD24) is a major endogenous ligand for CD33-family of Siglecs to protect the host against inflammatory and autoimmune diseases, metabolic disorders and most notably respiratory distress in COVID-19. The discoveries on CD24-Siglec interactions propelled active translational research to treat graft-vs-host diseases, cancer, COVID-19 and metabolic disorders. This mini-review provides a succinct summary on biological significance of CD24-Siglec pathway in regulation of inflammatory diseases with emphasis on clinical translation.